2022
DOI: 10.3389/fphar.2022.1051280
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins: New players in cancers

Abstract: Apolipoproteins (APOs), the primary protein moiety of lipoproteins, are known for their crucial role in lipid traffic and metabolism. Despite extensive exploration of APOs in cardiovascular diseases, their roles in cancers did not attract enough attention. Recently, research focusing on the roles of APOs in cancers has flourished. Multiple studies demonstrate the interaction of APOs with classical pathways of tumorigenesis. Besides, the dysregulation of APOs may indicate cancer occurrence and progression, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 193 publications
1
19
0
Order By: Relevance
“…TF has also shown as one of the promising markers due to better segregation with high accuracy in ML, and could further be correlated with altered iron metabolism and its link with cancer progression and metastasis [ 60 ]. Similarly, Apolipoprotein B (APOB), which is significantly altered in meningioma in our study, has been associated with cancers and brain tumors [ 61 , 62 ]. A study by Zhou et al illustrated the importance of apolipoprotein profiles and serum ferritin in maintaining homeostasis where the relationship was studied in the context of brain tumors and aggressiveness [ 63 ].…”
Section: Discussionsupporting
confidence: 56%
“…TF has also shown as one of the promising markers due to better segregation with high accuracy in ML, and could further be correlated with altered iron metabolism and its link with cancer progression and metastasis [ 60 ]. Similarly, Apolipoprotein B (APOB), which is significantly altered in meningioma in our study, has been associated with cancers and brain tumors [ 61 , 62 ]. A study by Zhou et al illustrated the importance of apolipoprotein profiles and serum ferritin in maintaining homeostasis where the relationship was studied in the context of brain tumors and aggressiveness [ 63 ].…”
Section: Discussionsupporting
confidence: 56%
“…Studies have suggested that apolipoproteins play critical roles in malignancies including GI cancers. Low apolipoprotein A1 level is linked to a high cancer risk, systemic inflammatory response and poorer survival in some cancers, including oesophageal squamous cell carcinoma 55 58 . This is in accordance with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a non-oncogenetic mutation of apolipoprotein B is observed, which can result in apolipoprotein B inactivation and is associated with the overexpression of oncogenic regulators and the downregulation of tumour suppressors, resulting in poorer survival outcomes. It is hypothesised that mutations that render apolipoprotein B inactive are preferred in tumorigenesis in order to provide more energy for cancer metabolism 55 , 65 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that elevated levels of ApoB/ApoA ratio associated with poor prognosis of PC. Recently, multiple studies have con rmed the dysregulation of Apolipoproteins (APOs) serving as potential biomarkers for cancer patients, indicating cancer occurrence and progression [32] . ApoB/ApoA ratio can re ect the interaction between individual atherogenic trend and anti atherosclerotic trend, and can more reveal the complex mechanism in the occurrence and development of atherosclerotic plaque than traditional lipid indicators [33] .…”
Section: Discussionmentioning
confidence: 99%